The Effect of Pre‐reading Instruction on Vocabulary Learning: An Investigation of L1 and L2 Readers' Eye Movements. Issue 1 (13th September 2020) - Pellicer‐Sánchez, Ana; Conklin, Kathy; Vilkaitė‐Lozdienė, Laura
Abstract: This study examined the effect of pre‐reading vocabulary instruction on learners' attention and vocabulary learning. We randomly assigned participants (L1 = 92; L2 = 88) to one of four conditions: pre‐reading instruction, where participants' received explicit instruction on six novel items and read a text with the items repeated eight times; reading‐only, where participants simply read the same text with the novel items repeated eight times; reading‐baseline, where participants read the same text with the repeated items replaced by known (control) words; and instruction‐only, where participants received explicit instruction on the novel items and read an unrelated text. Eye‐tracking was used to measure amount of attention to the vocabulary during reading. We assessed knowledge of the target vocabulary in three immediate posttests (form recognition, meaning recall, and meaning recognition). Results showed that pre‐reading instruction (plus reading the text) led to both more vocabulary learning and a processing advantage. Cumulative reading times were a significant predictor of meaning recognition scores. Abstract :